FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMBELI TERHADAP BENIH IKAN MAS (CYPRINUS CARPIO) DI BALAI BENIH IKAN LAWE BEKUNG KECAMATAN BADAR KABUPATEN ACEH TENGGARA - Hajrah Lestari; Hanisah; Silvia Anzitha (Bajang Institute, 2023)
This study aims to determine what factors influence the interest of buyers of carp (Cyprinus carpio) seeds at the Lawe Bekung Fish Seed Center, Badar District, Southeast Aceh Regency. This research was conducted at the Lawe Bekung Fish Seed Center, Badar District, Southeast Aceh Regency.This research was conducted using a survey method, namely by distributing questionnaires to respondents with a total sample of 30 respondent. The sampling technique used the side incidental method, which is technique carried out by “coincidence”. To find out what factors influence the buyer's interest in carp fry (Cyprinus carpio) at the Lawe Bekung Fish Seed Center, Badar District, Southeast Aceh Regency, statistical analysis using multiple linear regression method was used. Data processing was carried out using SPSS 20 computer software. Results esearch shows that the variabeles buyer tastes have a significant effect on the interest of buyers of carp seeds at the Lawe Bekung Fish seed Center, Badar District, Southeast Aceh Tenggara. And ths variables of price perception, seed quality, number of pependents and income have no significant effect on buyer Interest at Lawe Bekung Fish Seed Center, Badar District, Southeast Aceh Regency.